Pengaruh Umur Simpan Terhadap Kualitas Panggelong Dari Sipirok Kabupaten Tapanuli Selatan Sumatera Utara Dengan Kemasan Yang Berbeda - Harahap, Nurhasanah; Faridah, Anni; Holinesti, Rahmi (Faculty of Tourism and Hospitality - Universitas Negeri Padang, 2017)
This researchwas aimed to analyze the shelf life of panggelongtoward the quality of the different packaging (sikkut leaves, banana leaves, plastic, boxes, mica, styrofoam). This type of research was a true experiment by using complete randomized designmethod. Then, the data was tabulated and did Variant Analysis (ANOVA), if the result was different, then carried the Duncan test. The best result from the panggelongpackaging was in day- 0, because there was no physical damage.Theshelf life of panggelong on the sikkut leaves and banana leaves packaging were 2 days. It took 3 days by using plastic, it took 5 days by using boxes, mica, and styrofoam. It could be concluded that panggelong could not be taken as a souvenir for a long distance.Keywords: Packaging, Panggelong, Shelf Life